RESPONS PERTUMBUHAN TANAMAN HIAS ANTHURIUM ‘GELOMBANG CINTA’ (Anthurium plowmanii) PADA BEBERAPA KONSENTRASI BAP DAN FREKUENSI PEMBERIAN PUPUK DAUN - Warnita .; Netti Herawati (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2018)
Ornamental plants anthurium wave love great demand of society because the leaves are beautiful, unique and interesting. The edges of the leaves of anthurium generally with characteristic wavy. Anthurium plant growth stimulation can be enhanced by the application of growth regulators BAP and foliar fertilizers. The purpose of this study was to obtain a concentration of growth regulators BAP and best foliar fertilizer for growing ornamental plants anthurium. Experiments was carried out in the plant tissue culture laboratory of the Faculty of Agriculture, Andalas University from November 2015 to February 2016. Materials used in the love wave anthurium seeds, plant media are a mixture of soil, sand, compost 1: 1: 1 (v / v). Two-factor factorial experiment arranged in completely randomized design with three replications. The first factor was the concentration of BAP (0, 2.5, 5.0 and 7.5 mg/L) and the second factor was the frequency of giving leaf fertilizer (0, 1, 2 times). The variables observed were plant height, leaf width, root length and fresh weight of plants. The data were analyzed by analysis of variance followed by Honestly Significant Difference test 5%. The results showed that there is an interaction between BAP and the frequency of leaf fertilizer application to plant height and root length. The best BAP 2.50 mg/L for leaf width growth and 5.0 mg/L best to increase the fresh weight of plants. The best BAP concentration of 2.50 mg/L for leaf width growth and 5.0 mg/L is best for increasing the fresh weight of plants. Application of leaf fertilizer with a frequency of 2 times shows the highest plant heightKeywords: Anthurium, BAP, Concentration, Foliar fertilizer, Frequency